Synthesis of species-specific stress proteins by virulent strains of Listeria monocytogenes. - Sokolovic, Z (1990)
Listeriolysin is a virulence factor that appears to be necessary for the intracellular survival of Listeria monocytogenes. As shown in this investigation, listeriolysin is produced in only small amounts by clinical isolates of L. monocytogenes belonging to the serogroup 1/2a, but its synthesis can be induced by heat shock and to a lesser extent by oxidative stress. In addition to about 15 heat shock proteins that appear to be common to L. monocytogenes and Listeria species that are nonpathogenic for humans, at least five heat shock proteins are specifically coinduced with listeriolysin in all L. monocytogenes strains under heat shock conditions but not in the other Listeria species. One type of L. monocytogenes mutant blocked in the expression of listeriolysin failed to synthesize several of these specific heat shock proteins.